Monitorando a exploração garimpeira de ouro no Norte do Mato Grosso no período 2009-2018 : dinâmica e impactos ambientais - Almeida, Wladimir Hermínio de (2019)
Gold mining is responsible for providing livelihoods for the low-income population in many developing countries around the world, especially in tropical areas. In contrast, it is associated with negative impacts such as clearing of riparian forests, destruction of watercourses due to shore excavation and untreated effluent discharge, environmental and human contamination of mercury, favoring the transmission of infectious diseases such as malaria and negligence on complying with labor and environmental laws. The aim of the present study was to map and follow the evolution of artisanal and small-scale gold mining (ASGM) areas in northern Mato Grosso, Brazil, from 2009 to 2018, identifying densification zones and verifying the dynamics of the activity, its environmental impacts and correlation with the national gold market. It was performed by remote sensing using Geographic Information System (GIS) software and began with the survey of ASGM areas inspected on site by the Brazil’s Federal Police's expertise in Sinop, state of Mato Grosso. This case set have became basis to define the study area and as a control for ASGM map validation. Based on the common characteristics of the standard alluvial mining process, satellite images were examined by direct visual analysis, and the active ASGM areas were identified and demarcated by manual vector editing, and one active ASGM map per year was made. The mining zones were identified by joining the maps of each year in a single map of accumulated ASGM and a 10 km buffer around the polygons of this map were calculated. Negative impacts on protected areas, drainage degradation and respective permanent preservation areas (APP) were raised. To verify the current status of recovery of exploited areas, the total area of decommissioned MAPEO without a degraded area recovery project (PRAD) was raised. The evolution of MAPEO areas was correlated with the annual average price of gold in the domestic market and its environment impacts using generated linear mixed model (GLMM) in the R program. Eight mining zones were identified and in three of these zones ASGM threatened or encroached protected areas. There was an increase of 232% of MAPEO areas, from 4,018 ha to 13,369 ha. In terms of impacts, degraded drainage increased from 68 to 182 km, a positive variation of 166%, and degraded APPs increased from 549 to 1,596 ha, 191% growth. The non-PRAD decommissioned ASGM areas were 94% overall considering projects that were decommissioned in 2016 and not resumed by 2018. Drainages and their degraded APPs had a significant correlation (α=0,05) with the evolution of the ASGM areas independent of the mining zone. The dynamics of active ASGM areas showed a significant correlation (α=0,05) with gold price evolution, but there were different rates in the analysis by gold mining zone indicating that specific characteristics of each zone can act so that the explored area varies more or less as a function from the fluctuations of the gold market. The accelerated growth of ASGM areas has occurred in other South American countries that are part of the Amazon biome since 2000, as well as the negative impacts on the environment. The strong correlation of this evolution with domestic gold prices indicates that the pressure on natural resources can increase and aggravate damage mainly regarding aquatic ecosystems in the northern of Mato Grosso, in the case of keeping the uptrend of the gold prices. The high percentage of areas without PRAD indicate lack of post-closure supervision by the competent public agencies and possible ignorance by miners about the consequences of prolonging environmental impacts over time. There is an urgent need to alert authorities and local society about the disorderly growth of activity and its negative consequences on protected areas and water resources in order to encourage participatory monitoring programs with education and training for good practices in small scale mining alongside the strengthening of enforcement. Initiatives such as the requirement to the miners for certification of the legal, environmental, social and labor compliance by gold buyers can accelerate the transformation of the sector to a more modern level of environmental and socioeconomic sustainability.